2021
DOI: 10.1016/j.cllc.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of MLN0128 (Sapanisertib) and CB-839 HCl (Telaglenastat) in Patients With Advanced NSCLC (NCI 10327): Rationale and Study Design

Abstract: Introduction: There are currently no approved targeted therapies for lung squamous-cell carcinoma (LSCC) and KRAS-mutant lung adenocarcinoma (LUAD). About 30% of LSCC and 25% of KRAS-mutant LUAD exhibit hyperactive NRF2 pathway activation through mutations in NFE2L2 (the gene encoding NRF2) or its negative regulator, KEAP1. Preclinical data demonstrate that these tumors are uniquely sensitive to dual inhibition of glycolysis and glutaminolysis via mammalian target of rapamycin (mTOR) and glutaminase inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The phenomenon is the basis of an interesting therapeutic strategy [ 169 ]. Currently, phase 1 clinical trials have started to check the effect of the glutamine inhibitor telaglenastat (CB-839) in advanced NSCLC [ 170 ]. However, the preliminary results of the studies in an animal model showed that the use of CB-839 as monotherapy in lung tumors with the K-Ras mutation did not give satisfactory results; for this reason, it is suggested to include selective inhibitors of glycolysis as well [ 171 ].…”
Section: Overview Of Targeted Therapy For Nsclcmentioning
confidence: 99%
“…The phenomenon is the basis of an interesting therapeutic strategy [ 169 ]. Currently, phase 1 clinical trials have started to check the effect of the glutamine inhibitor telaglenastat (CB-839) in advanced NSCLC [ 170 ]. However, the preliminary results of the studies in an animal model showed that the use of CB-839 as monotherapy in lung tumors with the K-Ras mutation did not give satisfactory results; for this reason, it is suggested to include selective inhibitors of glycolysis as well [ 171 ].…”
Section: Overview Of Targeted Therapy For Nsclcmentioning
confidence: 99%
“…At the same time, for pathways that crosstalk with NRF2, preexisting compounds for these pathways can be used in combination with NRF2-directed compounds [13]. In fact, a phase I trial combining MLN0128 (sapanisertib), an mTOR inhibitor, and CB-839, a glutaminolysis inhibitor, is ongoing in patients with advanced NSCLC (KRAS-mutant LUAD and LUSC) having NFE2L2/KEAP1 mutations [234].…”
Section: Inhibitors Of Nrf2 Downstream Effectorsmentioning
confidence: 99%
“…The combination of drugs has achieved the effect of improving the efficacy and reducing the side effects of alkylating agents, which can be considered as a new strategy. In addition, the glutaminase inhibitor CB-839 has entered clinical trials for determining its safety and activity ( Riess et al, 2021 ).…”
Section: Interactionmentioning
confidence: 99%